Peran Vaksin Rotavirus terhadap Penurunan Jumlah Kasus dan Lama Rawat Anak dengan Diare: Analisis - Devana, Natasha Dianasari; Rizkia, Chaula Putri (PT Kalbe Farma Tbk., 2025)
Diarrhea remains one of the leading causes of morbidity and mortality among children in developing countries, including Indonesia. One of the most common causes of severe acute diarrhea is rotavirus infection, which is highly contagious through the fecal-oral route and can lead to severe dehydration and even death. Efective prevention can be achieved through rotavirus vaccination, which has been proven to reduce incidence, prevent transmission, and decrease disease severity. Rotavirus vaccination in children is known to be benefcial in controlling cases of rotavirus diarrhea, and since 2023, the rotavirus vaccine has been part of Indonesia's national immunization program, provided free of charge to infants according to the Ministry of Health's immunization schedule. Multiple studies have shown that this immunization reduces the risk of serious complications, shortens hospital stays, decreases hospitalization rates, and lessens the economic burden on families due to medical costs and lost productivity. Broad implementation of rotavirus vaccination is therefore a key strategy to improve child health and reduce diarrhea-related mortality in Indonesia.